The Effect of Effective Tax Rate, Profitability and Debt to Past Liabilitieshe - Septian Abdiansyah (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Abstract—The purpose of this research is to know and analyze the effect of effective tax rate on liabilities, to know and analyze the effect of profitability on liabilities, to know and analyze the effect of past debt on liabilities and to know and analyze the effect of effective tax rate, profitability, and past debt on liability. The method used in this study is a linear regression model using the help of Eviews version 10 software with testing details as follows: classic assumption test (normality, multicollinearity, and heteroscedasticity), multiple linear regression test, determination coefficient test (adjusted R2), hypothesis test (test t) and Hypothesis Test (Test F). The results of this study are effective tax rate variables with the proxy of current effextive tax rate have no significant effect on the dependent liability variable seen the probability value 0.8003> 0.05. Profitability variable with proxy ROA has a significant effect on the dependent variable liability with a probability value of 0.0007 <0.05. Past debt variable with past debt to asset proxy the previous year has a significant effect on the dependent variable liability with a probability value of 0.0002 <0.05. Variable effective tax rate, profitability and past debt simultaneously affect the liability of this case can be seen from the F table value is greater than F calculated that is the value of 2.67 <27.20076.